Public Sector Balance Sheet Strength and the Macro Economy - Yousefi, Seyed Reza (IMF Working Papers; Working Paper ;, 2019)
This paper introduces concepts of public sector balance sheet (PSBS) strength, taking into account different aspects of what governments own in addition to what they owe. It develops measures of PSBS strength and investigates their macroeconomic implications. Empirical estimations show that in their pricing of sovereign bonds, financial markets account for government assets and net worth in addition to their liabilities. Furthermore, economies with stronger public sector balance sheets experience shallower recessions and recover faster in the aftermath of economic downturns. This faster return to growth can be explained by the greater space for countercyclical fiscal policy in countries with stronger balance sheets.